A new book provides a roadmap for food systems transformation in Kenya - Anisimova, Evgeniya (International Food Policy Research Institute, 2024)
The past few years have seen Kenya, along with many other countries, confronted with multifaceted and compounding challenges. The disruptions caused by COVID-19, high levels of food price inflation, and environmental crises, such as locust infestations and droughts, have severely tested the resilience of Kenya’s food systems and the affordability of food for its citizens. Against this backdrop of challenges and ongoing demographic shifts, urbanization, and stagnating agricultural production, the need for reexamining the approach to Kenyan food systems has never been more critical. A new IFPRI book Food Systems Transformation in Kenya: Lessons from the Past and Policy Options for the Future responds to this imperative by bringing together a wealth of empirical research on various aspects of Kenya’s food systems and offering a comprehensive overview of their historical trajectories and possibilities for future evolution. The book, edited by Clemens Breisinger, Michael Keenan, Juneweenex Mbuthia, and Jemimah Njuki, was launched on January 8, 2024, in Nairobi, Kenya, during a hybrid event co-organized by IFPRI, the International Livestock Research Institute (ILRI), Kenya’s Ministry of Agriculture and Livestock Development (MoALD), and the CGIAR Initiative on National Policies and Strategies.